Sistema gerencial para eventos: proposta de um sistema para integrar informações e gerar indicadores para o mercado de entretenimento - Pereira, Rafael Liporace de Souza (2018)
This study analyzes the commercial and financial viability of SGE project management program (Management System for Events which is an integrated management software for the entertainment industry. The proposal is to be more than just a management system among many options offered, presenting itself as a focused product in a relevant cluster that does not have any system adapted to their real business needs. Based on the reality of Rio de Janeiro, SGE's business plan arose from the need of the entertainment market to group the management information spread across several independent systems, with the aim of obtaining historical, comparative and mainly indicators for a market that every day creates more relevance in the country and has been professionalizing year after year